Holly blues - Albert, Susan Wittig (Albert, Susan Wittig. China Bayles mysteries, 2010)
China Bayles is fit to spit when her husband's troubled ex-wife, Sally, shows up at her herb shop, claiming to be broke with nowhere else to turn. When she invites Sally to stay, China starts receiving menacing calls from an "ex" of Sally's, who seems to have a connection to the murder of her parents nearly a decade ago.